Literacy in the Era of Globalization Towards Learning Society in MTsN 3 Kota Tangerang - Ade Zaenudin (International Journal of Social Science, 2022)
Students' literacy scores in the globalized world are still very low based on several international assessments. The government responded by issuing several programs including the Gerakan Literasi Sekolah and Asesmen Nasional which contained an Asesmen Kompetensi Minimum (AKM) in the field of Literacy and Numeracy. This paper is the result of research on the implementation of the literacy movement in MTsN 3 Kota Tangerang using a naturalistic qualitative approach based on case studies through interviews, observations, and library studies. Based on the results of the study found that MTsN 3 Kota Tangerang is committed to implementing the literacy movement to meet the era of globalization towards the creation of a learning society. Some literacy programs include magazine publishing, book publishing, and some habituation programs that are carried out continuously. The real results of this literacy program include the birth of several writers from both teachers and students who hope to further increase literacy values both at the local and global levels.